2018
DOI: 10.1007/s10439-018-2015-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Metric for Predicting Brain Strain Responses Using Head Kinematics

Abstract: Diffuse brain injuries are caused by excessive brain deformation generated primarily by rapid rotational head motion. Metrics that describe the severity of brain injury based on head motion often do not represent the governing physics of brain deformation, rendering them ineffective over a broad range of head impact conditions. This study develops a brain injury metric based on the response of a second-order mechanical system, and relates rotational head kinematics to strain-based brain injury metrics: maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 24 publications
0
59
0
Order By: Relevance
“…Probabilistic evaluation approaches, comparable to (Forman et al 2012) should be developed for the long bones to enable the application of HBMs for the virtual testing of cyclist safety. Furthermore, a probabilistic brain injury criterion should be applied, either based on a FE brain model (Sahoo et al 2016) or on rotational loads (Gabler et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic evaluation approaches, comparable to (Forman et al 2012) should be developed for the long bones to enable the application of HBMs for the virtual testing of cyclist safety. Furthermore, a probabilistic brain injury criterion should be applied, either based on a FE brain model (Sahoo et al 2016) or on rotational loads (Gabler et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…strain history within the brain) during an impact, which has been correlated to injury using metrics such as cumulative strain damage measure 2,46 and the universal BrIC (UBrIC). 16 Along with validated head models and injury prediction tools, there is a need for validated helmet models to more fully exploit modeling and simulation in the study of head injuries in contact sports. Because helmet rating agencies and head injury metrics both rely on head kinematics to determine injury risk, it is important to use kinematics to validate FE models of helmets.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the 95th percentile MPS is reported to alleviate the extracted responses in the ROIs from being driven by the response of a single element. As reported by Gabler and colleagues, 64 compared with the 95th percentile strain, the 50th percentile strain may be more indicative of the average deformation level. Thus, the 50th percentile MPS in the simulations of axial rotations are further checked.…”
Section: Figmentioning
confidence: 82%